Less is more: Optimising the biocementation of coastal sands by reducing influent urea through response surface method - Ashraf, M.S. (Elsevier Ltd, 2021)
The excessive effluent ammonia produced during the conventional biocementation of coastal sands by ureolytic Microbially Induced Calcite Precipitation (MICP) poses a looming threat to the marine environment. This research mitigates this threat by employing a brute force deployment of the Response Surface Method (RSM) for optimal minimisation of urea, which is the primary contributor of this effluent ammonia, to develop a sustainable MICP treatment model for the biocementation of coastal sand columns. The unconfined compressive strength (UCS) and calcium carbonate content (CCC) results of these columns, measured during their UCS and gravimetric acid washing testing, were used in this developed model for its validation and further optimisation. The biocementation solution resulting from this finally optimised MICP model used 75 lesser influent urea per gram of sand than its predecessor treatment model and still significantly improved the UCS of biocemented sand columns (from 0 kPa to 111.63 kPa). The structural analyses (XRD, FESEM) of these biocemented columns showed the adsorption of calcium carbonate and nesquehonite crystals on sand grains. This reduction in the consumption of urea significantly lowers the production of effluent ammonia during the biocementation of coastal sands. Therefore, it is suggested that this optimised MICP treatment model offers a sustainable method for strengthening coastal sands with little to no effect on the natural mosaic of their subsurface ecosystems. Â© 2021 Elsevier Ltd